2021
DOI: 10.1017/sjp.2021.27
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Institutionalized Adolescents: The Role of Memories of Warmth and Safeness, Shame and Self-criticism

Abstract: Institutionalization is a current problem, related to several indicators of psychological maladjustment. In the same way, there are several studies that point to the role of shame and self-criticism in the development of psychopathology. Therefore, our study explored, in institutionalized adolescents, whether early memories of warmth and safeness (EMWS) were associated to depression through external shame and self-criticism. The sample included 171 institutionalized adolescents (60.2% girls; Mage = 15.56; SD =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
4
0
3
Order By: Relevance
“…Later studies also confirmed that self-criticism functions as an important mediator in the relationship between shame memory and depression [44]. In the research results of Santos et al [13], self-criticism is a complete mediator between shame memory and depression.…”
Section: The Mediating Role Of Self-criticism Between Shame Memory An...mentioning
confidence: 78%
See 2 more Smart Citations
“…Later studies also confirmed that self-criticism functions as an important mediator in the relationship between shame memory and depression [44]. In the research results of Santos et al [13], self-criticism is a complete mediator between shame memory and depression.…”
Section: The Mediating Role Of Self-criticism Between Shame Memory An...mentioning
confidence: 78%
“…A recent study also noted that self-criticism, which may take various forms and serve different purposes, is closely tied to shame memory. The first is that the "Inadequate Self" is typically used to rectify acts when one feels unhappy or upset about them for the mistakes one makes; the second is that when one's ego is judged to be abhorrent, flawed, and worthless, it is typically intended to harm and attack oneself [13]. Blatt (1974) [14] systematically discussed the close connection between self-criticism and many mental health issues in his research on the relationship between personality and depression.…”
Section: The Mediating Role Of Self-criticism Between Shame Memory An...mentioning
confidence: 99%
See 1 more Smart Citation
“…A violência intrafamiliar e a exposição à violência são consideradas fatores de risco para reprodução de comportamentos violentos tanto as situações de maus tratos presenciadas na violência entre os pais quanto as sofridas diretamente pela criança ou adolescente 1,19 .…”
Section: Discussionunclassified
“…Portanto, por se tratar de um período de importantes transformações para a vida adulta, que envolvem mudanças biológicas, sociais e, principalmente, psicológicas para toda a vida, não deve ser reduzido a uma simples faixa etária. Nesse ponto, a institucionalização surge como um problema atual relacionados a diversos fatores socioeconômicos e de desajustes psicoló-gicos 1 .…”
Section: Introductionunclassified